HIV-gp140-Specific Antibodies Generated From Indian Long-Term Non-Progressors Mediate Potent ADCC Activity and Effectively Lyse Reactivated HIV Reservoir - Dhande, Jayshree R.; Bagul, Rajani D.; Thakar, Madhuri R. (Frontiers in Immunology, 2022)
Strategies to reduce the human immunodeficiency virus (HIV) reservoir are urgently required. The antibody-dependent cellular cytotoxicity (ADCC)-mediating anti-HIV antibodies have shown an association with HIV control. We assessed if such antibodies can be generated in vitro and whether the generated antibodies can facilitate the reduction of reactivated HIV reservoir. We isolated HIV-1-gp140-specific memory B cells from HIV-1-infected long-term non-progressors (LTNPs) with or without plasma ADCC and cultured them to generate anti-HIV antibodies. The ability of the generated antibodies to mediate ADCC and facilitate NK cell-mediated lysis of reactivated HIV reservoir was assessed by the rapid fluorometric antibody-dependent cellular cytotoxicity assay and a flow-based novel latency reduction assay, respectively. All LTNPs showed the presence of gp140-specific memory B cells [median: 0.79% (0.54%–1.225%)], which were successfully differentiated into plasma cells [median 72.0% (68.7–82.2%)] in an in-vitro culture and secreted antibodies [median OD: 0.253 (0.205–0.274)]. The HIV-gp140-specific antibodies were generated from 11/13 LTNPs irrespective of their plasma ADCC status. The generated antibodies from LTNPs with plasma ADCC showed higher ADCC potency (median: 37.6%, IQR: 32.95%–51%) and higher reduction in reactivated HIV reservoir (median: 62.5%, IQR: 58.71%–64.92%) as compared with the antibodies generated from LTNPs without plasma ADCC (ADCC: median: 8.85%, IQR: 8%–9.7%; and % p24 reduction median: 13.84, IQR: 9.863%–17.81%). The potency of these antibodies to reduce latent reservoir was two-fold higher than the respective plasma ADCC. The study showed that the potent ADCC-mediating antibodies could be generated from memory B cells of the LTNPs with plasma ADCC activity. These antibodies also showed potent ability to facilitate NK cell-mediated lysis of reactivated HIV reservoirs. It also indicated that memory B cells from individuals with plasma ADCC activity should be preferentially used for such antibody generation. The important role of these antibodies in the reduction of latent reservoirs needs to be further evaluated as a useful strategy to obtain a functional cure for HIV infection.